An experimental study: quantitatively evaluating the change of the content of collagen fibres in penis with two‐dimensional ShearWave™ Elastography. (12th July 2016) - Qiao, X.‐H.; Zhang, J.‐J.; Gao, F.; Li, F.; Bai, M.; Du, L.‐F.; Xing, J.‐F.
Summary: The purpose of this study was to explore the value of two‐dimensional ShearWave ™ Elastography (2D‐SWE) on quantitatively evaluating the change of the content of collagen fibres in penis. Twenty male Sprague Dawley rats were divided into the pre‐sexual maturity group (Group 1) and the sexual decline group (Group 2) according to age. The ultrafast ultrasound device Aixplorer ® (SuperSonic Imagine, Aix‐en‐Provence, France) was used for 2D‐SWE imaging of penis, and the measurement index was shear wave stiffness (SWS). The immunohistochemistry was used to analyse the content of collagen fibres in penis, and the measurement index was positive area percentage (PAP). The differences of SWS between the two groups and PAP between the two groups were analysed. SWS of Group 1 and Group 2 was 10.18 ± 1.09 and 8.02 ± 1.34 kPa, and SWS of Group 2 was significantly lower than Group 1 ( p  <   .01). PAP of Group 1 and Group 2 was 4.83 ± 3.61% and 16.41 ± 10.02%, and PAP of Group 2 was significantly higher than Group 1 ( p  <   .01). Our results indicate that when the content of collagen fibres changes, SWS of penis measured with 2D‐SWE would change significantly as well. Two‐dimensional SWE can be used to quantitatively evaluate the change of the content of collagen fibres in penis.